Climate influence on flooding and drainage processes in urban construction - V. I. Sologaev (Вестник СибАДИ)
Introduction. Flooding of built-up and developing city areas with groundwater is an unfavorable process in our country and around the world. The groundwater level (GWL) rises to the surface of the earth. The consequences of increasing the groundwater level are dangerous for humans and the environment. Drainage of urban areas leads to a decrease in groundwater level. Drainage systems are an active protection against flooding with groundwater. Climate affects the processes of flooding and drainage in urban construction. This influence is taken into account too little in the current building codes and calculation methods for designers, builders and employees of urban services. A lot of materials have been accumulated that require scientific publication due to their relevance for further improvement ways to withstand flooding of urban and populated areas with groundwater with climate considering. Ineffective situations of extensive protection against sudden onset flooding are observed all over the world every year. It is necessary to strengthen the role of scientific approaches in making the choice of appropriate measures to keep save against flooding. Paying attention to the climate influence on flooding and drainage processes in urban construction can make a significant contribution in this direction.Methods and materials. The urban man-made environment differs considerably from the natural before construction, most of all in flooding and drainage of territories, buildings and structures. Therefore, the theory of filtration in urban construction requires improvement of the methodology of forecasting, calculating and modeling flooding and drainage, especially paining attention to the climate of cities, which is still almost not taken into account in the development of protective measures. This paper presents new ideas and their implementation on the stated research theme. This opens a new direction of scientific methodology related to flood protection in urban construction with the consideration of climate influence. New ideas cannot be implemented in one article, since the problem is very extensive. Therefore, in the future, it is expected that other scientific studies will be published on this current theme, planned as a direction of promising and relevant scientific research.Discussion. In the course of the study, the characteristics of the city climate that can affect the processes of flooding and drainage of groundwater in built-up and developing city areas has been considered.The impact of the Sun is very significant. Sun rays, passing through the atmosphere, affect the groundwater regime. The share of solar energy is several times of magnitude greater than the influence of the temperature gradient coming from the depths of the Earth to the earth's surface. The impact of sunlight is expressed in the form of solar radiation. In this case, the albedo of the irradiated surfaces has an effect. Urban development creates significant shading of the soil surface with a subsequent decrease in evaporation and an increase in moisture infiltration to groundwater. The wind regime of the development changes. This has been taken into account in the presented methodology of the article, the necessary dependencies and examples of calculating the reduction of water evaporation from the soils of the foundations of buildings and structures are given. New experimental measurements on the theme of the study, as well as author’s innovative devices and instruments have been considered.Conclusion. Thus, a new direction of scientific methodology related to protection from flooding in urban construction has been discovered, taking into account the climate change of the technogenic environment of the built-up and developing city areas. The presented work should be considered as a pioneering article, giving in the first approximation a new methodology for the considering the influence of climate on the processes of flooding and drainage in urban construction. Therefore, in the future, it is expected that other scientific works will be published on this acute topic, planned in the direction of promising and relevant scientific research.